REKONSTRUKSI TAFSÎR MAWDÛ‘Î: Asumsi, Paradigma, dan Implementasi - Yardho, Moh. (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2019)
The current of modernization has an impact on almost every joint of human life. The problems that are generated are increasingly developing and complex, which requires the Qur’an to provide a solution. This point is closely related to the Qur’anic interpretation methodology that is appropriate for responding and providing solutions in accordance with the problems that occur. The methodology of thematic interpretation (tafsîr mawdû‘î) is one of the choices. Tafsîr mawdû‘î is one of the interpretation methodologies needed in the modern era. The advantage is that besides being able to frame various verses of the Koran into a whole unit, it can also focus on verses that discuss a theme substantially and comprehensively to answer one problem. This article descriptively-analytically reconstructs tafsîr mawdû‘î, both assumptions, paradigms, their implementation. This article reveals the narrative of the solution of tafsîr mawdû‘î for contemporary problems in a more structured, comprehensive and objective perspective in the Qur’an, so that the reconstruction of the tafsîr mawdû‘î method is more targeted.[Arus modernisasi berdampak pada hampir di setiap sendi kehidupan manusia. Problematika yang ditimbulkan kian berkembang dan kompleks, yang menuntut Alquran dapat memberikan solusinya. Poin ini terkait erat dengan metodologi interpretasi Alquran yang tepat untuk merespons dan memberikan solusi sesuai dengan problematika yang terjadi. Metodologi tafsir tematik (tafsîr mawdû‘î) menjadi salah satu pilihannya. Tafsîr mawdû‘î merupakan salah satu metodologi tafsir yang diperlukan di era modern saat ini. Kelebihannya adalah selain mampu membingkai pelbagai ayat Alquran menjadi satu-kesatuan yang utuh juga dapat memfokuskan ayat yang membahas suatu tema secara substansial dan komprehensif untuk menjawab satu persoalan. Artikel ini secara deskriptis-analitis merekonstruksi tafsîr mawdû‘î, baik asumsi, paradigma, implementasinya. Artikel ini menguak narasi solusi dari tafsîr mawdû‘î atas problematika kekinian secara lebih terstruktur, komprehensif, dan objektif dalam perspektif Alquran, sehingga rekonstruksi metode tafsîr mawdû‘î lebih tepat sasaran]